Staging representations: Reflections on performing activism in a visual art and theatre collaboration. Issue 1 (1st July 2018) - Listengarten, Julia; Watson, Keri
This article explores sites of possibility for addressing the current refugee crisis through artistic collaborations and asks how we as artists negotiate artistic mediums to foster a collective dialogue about ethics of representation concerning migrant bodies and mediatized images of violence and destruction. In winter 2018, University of Central Florida's Schools of Visual and Performing Arts offered interdisciplinary programming that addressed issues of exile, displacement and Otherness. The gallery exhibition Finding Home: The Global Refugee Crisis brought together fourteen artists from around the world whose work addresses themes including borders as geographical and symbolic dividing lines, displacement and asylum seeking, refugee camps and detention centres, and immigration and resettlement. The theatre production of David Edgar's Pentecost and the staged reading of The Refugee Plays interweaved the past with the present to challenge how society responds to a refugee crisis and treats 'precarious bodies' of the displaced and wounded. This article considers the ways in which this collaboration united the visual and performing arts, decolonized the institution, adapted, transformed and negotiated media, performed difference and diversity, and demonstrated the ability of the arts to act for social justice.